2004
DOI: 10.1007/s00284-004-4377-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Ex Vivo Phagocytic Capacity of Peritoneal Leukocytes in Mice by Oral Delivery of Various Lactic-Acid-Producing Bacteria

Abstract: Lactic-acid-producing bacteria (LABs) are known to have immunomodulating activity. In the current study, various LABs were tested for their immunity-enhancing activity, especially the phagocytic activity of leukocytes. Viable but not heat-killed cells of Weissella kimchii strain PL9001, Lactobacillus fermentum strain PL9005, and L. plantarum strain PL9011 significantly increased the ex vivo phagocytic capacity of mouse peritoneal leukocytes to ingest fluorescein isothiocyanate (FITC)-labeled Escherichia coli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This is an essential activity of polymorphonuclear cells and monocytes-macrophages in innate immunity. Similar results have been reported using different labeled bacteria as well as Escherichia coli [55]. A previous study also documented a significant increase in phagocytosis after treatment with different strains of Lactobacillus both in vitro and in vivo [56][57][58].…”
Section: Discussionsupporting
confidence: 88%
“…This is an essential activity of polymorphonuclear cells and monocytes-macrophages in innate immunity. Similar results have been reported using different labeled bacteria as well as Escherichia coli [55]. A previous study also documented a significant increase in phagocytosis after treatment with different strains of Lactobacillus both in vitro and in vivo [56][57][58].…”
Section: Discussionsupporting
confidence: 88%
“…Administration to mice with two B . strains of lactobasilli isolated from healthy centenarians enhanced NK cell activity and phagocytic activity of macrophages (204), and coupled with probiotics L. fermentum strain PL9005 and L. plantarum strain PL9011 enhanced the phagocytic capacity of peritoneal leukocytes (205). Mice receiving L. paracasei NTU 101 (10 8 CFU/d) for 6 or 9 wk showed higher expression of DC maturation markers (MHC-II hi , CD80 + , and CD86 + ) and NK group-2D (NKG2D), as well as enhanced lymphocyte proliferation in response to L. paracasei Ag (206), which together suggest that probiotics may enhance specific immunity by promoting APC function.…”
Section: Modulation Of Immune Function By Nutrients and Food Componentsmentioning
confidence: 99%
“…achieve this beneficial effect by acting on the mucosal immune system, in particular DCs and NK cells (271). As an example, it has been shown that administration of lactobacilli to mice can enhance the immune function in mice by increasing NK cell activity and phagocytic activity of macrophages (272), as well as enhance the phagocytic capacity of peritoneal leukocytes (273), increase the expression of DC-maturation markers, and enhance lymphocyte proliferation (274). Consistent with studies using animal models, human studies also showed that probiotic use could have a positive effect on the immune system.…”
Section: Role Of Probiotics Diet and Fasting In Immune Function The mentioning
confidence: 99%